Resin composition, prepreg, and composite material

By using a composition of an epoxy diluent and a functional resin in an epoxy resin system, the problems of uneven dispersion and poor bonding properties of the filler are solved, and the excellent bonding and processing properties of the composite material are achieved.

CN119708757APending Publication Date: 2025-03-28ZHEJIANG WAZAM NEW MATERIAL CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311296096.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Uneven dispersion of fillers in the epoxy resin system leads to layering of composite materials, and the introduction of fillers increases the cross-linking curing conditions, affecting bonding.

Method used

By using a resin composition containing an epoxy diluent and a functional resin, filler dispersion and epoxy group reactive activity are improved by limiting the molecular weight of the epoxy diluent and the structure of the functional resin.

Benefits of technology

The uniform dispersion of fillers in the resin system is achieved, the composite material layering is avoided, and the bonding and processing performance of the composite material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004483030520000021
    Figure BDA0004483030520000021
  • Figure BDA0004483030520000041
    Figure BDA0004483030520000041
  • Figure BDA0004483030520000121
    Figure BDA0004483030520000121
Patent Text Reader

Abstract

The invention relates to a resin composition which comprises epoxy resin, functional resin, an epoxy diluent, filler and a curing agent, wherein the molecular weight of the epoxy diluent is less than or equal to 270, the structural formula of the functional resin is shown as a formula (I) or a formula (II), in the formula (I) and the formula (II), n is an integer of 1-3, R1 and R2 are electron donating groups, and R3 is alkyl, epoxy group or carboxyl with the carbon chain length less than or equal to 4. The invention also provides a prepreg and a composite material. The filler in the resin composition is good in dispersity, and the composite material prepared from the resin composition has excellent binding property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, in particular to a resin composition, a prepreg and a composite material. Background Art

[0002] Epoxy resin is widely used in the preparation of components for consumer electronic products due to its excellent comprehensive properties such as heat resistance and formability. Based on the requirements of mechanical properties and cost reduction, fillers are generally added to the epoxy resin system, but the introduction of fillers usually makes the dispersion of the components in the epoxy resin system worse. If the filler is unevenly dispersed in the resin system, it is easy to cause stratification of the composite material. At the same time, the introduction of fillers makes the conditions required for epoxy cross-linking and curing higher, affecting its cross-linking and curing reaction, resulting in poor bonding of the composite material and inability to process subsequent components. Summary of the invention

[0003] Based on this, it is necessary to provide a resin composition, a prepreg and a composite material to address the above problems. The filler in the resin composition has good dispersibility, and the composite material prepared using the resin composition has excellent bonding properties.

[0004] A resin composition comprises an epoxy resin, a functional resin, an epoxy diluent, a filler and a curing agent; wherein the molecular weight of the epoxy diluent is ≤270, and the structural formula of the functional resin is as shown in formula (I) or formula (II):

[0005]

[0006] In formula (I) and formula (II), n is an integer of 1 to 3, R1 and R2 are electron-donating groups, and R3 is an alkyl group, epoxy group or carboxyl group with a carbon chain length of ≤4.

[0007] In one embodiment, the epoxy functionality of the functional resin is ≥2 and / or the epoxy equivalent is ≤300;

[0008] And / or, R1 and R2 are independently selected from -O-, acyloxy or alkoxy.

[0009] In one embodiment, the epoxy diluent has a benzene ring structure in its molecular chain and contains only one terminal epoxy group.

[0010] In one embodiment, the epoxy diluent is selected from at least one of benzyl glycidyl ether, phenyl glycidyl ether, o-cresol glycidyl ether or p-tert-butylphenyl glycidyl ether.

[0011] In one embodiment, based on 85 to 95 parts by weight of the epoxy resin, the amount of the functional resin is 5 to 15 parts by weight, the amount of the filler is 40 to 100 parts by weight, the amount of the curing agent is 2 to 40 parts by weight, and the amount of the epoxy diluent is 5 to 15 parts by weight.

[0012] In one of the embodiments, the mass ratio of the epoxy diluent to the filler is 1:10 to 1:15.

[0013] In one embodiment, the surface of the filler also has a coating layer made of rubber elastic body;

[0014] And / or, the resin composition further comprises a curing accelerator.

[0015] In one embodiment, the rubber elastomer is selected from at least one of hydroxy-terminated nitrile rubber, carboxyl-terminated nitrile rubber, polysulfide rubber, polyurethane rubber, polybutadiene core-shell rubber, nitrile-isocyanate or amino polyamide.

[0016] In one of the embodiments, the mass ratio of the coating layer to the filler is 1:10 to 1:100.

[0017] In one embodiment, the curing accelerator is selected from at least one of tertiary amines, Lewis acid-amine complexes, dicyandiamide-urea complex modifiers, phenol, imidazole, imidazole derivatives, or acetylacetone metal complexes.

[0018] In one embodiment, the curing accelerator is selected from imidazole derivatives; or, the curing accelerator contains 50% to 80% by mass of at least one of Lewis acid-amine complex, dicyandiamide-urea complex modification or acetylacetone metal complex.

[0019] A prepreg made from the resin composition.

[0020] A composite material made from the prepreg.

[0021] In the resin composition provided by the present invention, by introducing an epoxy diluent and limiting its molecular weight, the dispersibility of the filler in the resin system can be effectively improved, the influence of the van der Waals force between molecules can be reduced, and the interface interaction between inorganic and organic substances can be improved, thereby avoiding the occurrence of stratification inside the composite material; and the epoxy diluent is beneficial to promoting the reactivity of the epoxy group in the resin system, and by introducing a functional resin with a specific structure, the electrophilic effect of the functional resin can be enhanced, the influence of steric hindrance can be reduced, and the reactivity of the epoxy group can be improved, thereby improving the bonding property of the composite material.

[0022] Therefore, the composite material prepared by using the resin composition has excellent bonding performance and thus has excellent processing performance. DETAILED DESCRIPTION

[0023] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0025] The present invention provides a resin composition, comprising an epoxy resin, a functional resin, an epoxy diluent, a filler and a curing agent; wherein the molecular weight of the epoxy diluent is ≤270, and the structural formula of the functional resin is as shown in formula (I) or formula (II):

[0026]

[0027] In formula (I) and formula (II), n is an integer of 1 to 3, R1 and R2 are electron-donating groups, and R3 is an alkyl group, epoxy group or carboxyl group with a carbon chain length of ≤4.

[0028] The resin composition provided by the present invention adds a specific functional resin and an epoxy diluent to the epoxy resin, so that the filler can be evenly dispersed in the resin system. The composite material prepared by using the resin composition is not stratified, and the composite material has excellent bonding properties, and thus has excellent processing performance.

[0029] Specifically, by introducing an epoxy diluent and limiting its molecular weight, the dispersibility of the filler in the resin system can be effectively improved, the influence of the intermolecular van der Waals force can be reduced, and the interface interaction between inorganic and organic substances can be improved, thereby avoiding the delamination of the composite material.

[0030] At the same time, by introducing functional resins and limiting the structure of functional resins, combined with epoxy diluents, the reactivity of epoxy groups can be promoted, the curing reaction rate and curing crosslinking density can be increased, thereby improving the reactivity of the resin system and the curing agent. Specifically, by limiting the functional resin to have a cyclic conjugated structure, and the epoxy group and the electron-donating group R1 are both located at the same substitution position, the electrophilic effect of the functional resin can be enhanced and the influence of steric hindrance can be reduced. At the same time, the electron-donating group R2 and R3 with a carbon chain length of ≤4 make the electrophilic effect during the reaction stronger than the steric hindrance effect, thereby improving the reactivity of the epoxy group, accelerating the curing reaction rate, and making the resin composition have an excellent degree of curing, thereby improving the bonding of the composite material.

[0031] Optionally, based on 85 to 95 parts by weight of the epoxy resin, the amount of the functional resin is 5 to 15 parts by weight, the amount of the filler is 40 to 100 parts by weight, the amount of the curing agent is 2 to 40 parts by weight, and the amount of the epoxy diluent is 5 to 15 parts by weight.

[0032] Optionally, the epoxy resin is preferably at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin or multifunctional epoxy resin.

[0033] Optionally, the curing agent is preferably at least one of phenolic acid, diaminodiphenylmethane, diaminodiphenyl sulfone, dicyandiamide, anhydride curing agent, β-hydroxymethyldiethylenetriamine, urea compounds or cationic curing agent. Further preferably, the cationic curing agent is selected from at least one of boron trifluoride, hexafluoroantimonate or Lewis acid; the urea compound is selected from at least one of N,N"-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) or 3-(3,4-dichlorophenyl)-1,1-dimethylurea; the anhydride curing agent is selected from at least one of methyltetrahydrophthalic anhydride or methylhexahydrophthalic anhydride.

[0034] Optionally, the epoxy functionality of the functional resin is ≥2 and / or the epoxy equivalent is ≤300, so as to further improve the reactivity of the epoxy group of the functional resin in the resin composition, increase the curing rate, and further improve the bonding property of the composite material.

[0035] Optionally, in the functional resin, R1 and R2 are independently selected from -O-, acyloxy or alkoxy.

[0036] Optionally, the epoxy diluent has a benzene ring structure in its molecular chain and contains only one terminal epoxy group. This arrangement can better improve the dispersibility of the filler in the resin system, reduce the influence of the intermolecular van der Waals force, increase the curing rate, and at the same time, improve the interface interaction between inorganic and organic substances, thereby improving the bonding performance of the composite material.

[0037] Optionally, the epoxy diluent is preferably at least one of benzyl glycidyl ether, phenyl glycidyl ether, o-cresol glycidyl ether or p-tert-butylphenyl glycidyl ether.

[0038] Optionally, the filler is preferably at least one of boron nitride, silicon dioxide or talc.

[0039] Optionally, the filler may also be a flame retardant filler, so that the prepared flame retardant epoxy resin has excellent bonding and excellent flame retardant properties. Optionally, the flame retardant filler is preferably at least one of phosphate, phosphite, phosphazene, melamine, melamine cyanuric acid, silicone, aluminum hydroxide, magnesium hydroxide, silicate or nitrogen-phosphorus-silicon ternary synergistic flame retardant.

[0040] Optionally, the mass ratio of the epoxy diluent to the filler is 1:10 to 1:15, which can improve the dispersibility while controlling the curing reaction rate of the resin system to ensure that the composite material has good bonding properties.

[0041] Optionally, the surface of the filler further has a coating layer formed of a rubber elastic body, and / or the resin composition further includes a curing accelerator.

[0042] Among them, when the rubber elastomer is used to coat the filler, it can be partially coated or completely coated to form a core-shell structure. Preferably, it is completely coated to form a core-shell structure, so as to avoid filler agglomeration, make the filler evenly dispersed in the resin system, improve the dispersibility of the filler in the resin system, and further improve the bonding of the composite material.

[0043] Optionally, the rubber elastomer is preferably at least one of hydroxy-terminated nitrile rubber, carboxyl-terminated nitrile rubber, polysulfide rubber, polyurethane rubber, polybutadiene core-shell rubber, nitrile-isocyanate or amino polyamide.

[0044] Optionally, the rubber elastic body further preferably contains active groups that can react with the epoxy resin in the molecular chain, thereby improving the dispersion of the filler and further promoting the reactivity and curing rate of the epoxy resin system, wherein the active groups are preferably hydroxyl groups and / or amine groups. For example, the rubber elastic body is preferably at least one of hydroxy-terminated nitrile rubber or nitrile-isocyanate.

[0045] Optionally, the mass ratio of the coating layer to the filler is preferably 1:10 to 1:100, which can further improve the coating effect of the rubber elastomer and improve the dispersibility of the filler in the resin system, while preventing the rubber elastomer from affecting the curing rate and degree of curing of the resin system, thereby affecting the bonding of the composite material.

[0046] Wherein, when the resin composition further includes a curing accelerator, it can be helpful to improve the curing rate and curing degree of the resin system, and further improve the bonding property of the composite material.

[0047] Optionally, the curing accelerator is preferably at least one of tertiary amines, Lewis acid-amine complexes, dicyandiamide-urea complex modifiers, phenol, imidazole, imidazole derivatives or acetylacetone metal complexes.

[0048] Optionally, when one curing accelerator is used, the curing accelerator is preferably an imidazole derivative; when two or more curing accelerators are used for compounding, the curing accelerator contains 50% to 80% of at least one of Lewis acid-amine complex, dicyandiamide-urea complex modifier or acetylacetone metal complex, by mass fraction, thereby further improving the curing rate and degree of curing of the composite material, improving the curing efficiency and improving the bonding of the composite material.

[0049] Optionally, based on 85 to 95 parts by weight of the epoxy resin, the amount of the curing accelerator is 0.2 to 1.7 parts by weight, and more preferably 0.3 to 1.1 parts by weight.

[0050] Optionally, the mass ratio of the curing agent to the curing accelerator is preferably 100:1 to 2:1, and more preferably 11:1 to 3:1, so that the curing rate of the resin composition is increased through the synergistic effect of the curing agent and the curing accelerator, and the bonding of the composite material is further improved.

[0051] Optionally, the resin composition also includes an auxiliary agent, which is preferably at least one of a silane coupling agent, a surfactant or a dispersant, so as to be more conducive to the uniform dispersion of the components in the resin composition, prevent the agglomeration of the components in the resin composition, thereby enhancing the interaction between the resin system and the filler, and further improving the bonding of the composite material.

[0052] The present invention also provides a prepreg made of the resin composition as described above. The present invention does not limit the specific preparation method of the prepreg using the resin composition. Preferably, the prepreg is obtained by impregnating or coating a reinforcing material with the resin composition and drying. The type of the reinforcing material is not limited, and is preferably at least one of glass fiber cloth, aramid cloth or carbon fiber cloth.

[0053] The present invention also provides a composite material made of the prepreg as described above. The present invention does not limit the specific preparation method of the composite material. Preferably, one or more prepregs are stacked, and release films are laid on both sides and placed in a mold. The composite material is cured and molded at a certain pressure and temperature for a certain time, and the release film is removed to obtain the composite material. Preferably, the pressure is preferably 0.5MPa to 1.5MPa, the temperature is preferably 120°C to 140°C, and the pressing time is preferably 4min to 6min.

[0054] Hereinafter, the resin composition, prepreg and composite material will be further described through the following specific examples.

[0055] Example 1

[0056] 4 parts by weight of butyronitrile-isocyanate were fully stirred and dissolved in propylene glycol methyl ether, and then 94 parts by weight of phosphazene were added and stirred at high speed to obtain a filler coated with a rubber elastic body.

[0057] A filler coated with a rubber elastomer, 85 parts by weight of a bisphenol A epoxy resin, 5 parts by weight of a functional resin of formula (I), wherein n is 2, R1 and R2 are both -O-, R3 is an epoxy group with a carbon chain length of 3 and an epoxy equivalent of 271, 2 parts by weight of N,N"-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea), 7 parts by weight of benzyl glycidyl ether, 0.1 parts by weight of a Lewis acid-amine complex, 0.1 parts by weight of imidazole and 0.5 parts by weight of KH550 are added to 30 parts by weight of propylene glycol methyl ether and stirred for 2 hours to mix evenly to obtain a resin composition.

[0058] The resin composition was uniformly coated on a glass fiber cloth and baked at 125° C. to obtain a prepreg.

[0059] Four layers of semi-cured sheets are stacked to form a semi-cured layer, and release films are laid on both sides of the semi-cured layer. The semi-cured layer is placed in a mold for curing and molding at a pressure of 0.5 MPa and a mold temperature of 130°C. After complete curing, the release film is removed to obtain a composite material.

[0060] The test results of the composite material of this embodiment are shown in Table 1.

[0061] Example 2

[0062] 1 part by weight of polyurethane rubber was fully stirred and dissolved in propylene glycol methyl ether, and then 80 parts by weight of phosphazene was added and stirred at high speed to obtain a filler coated with a rubber elastic body.

[0063] A filler coated with a rubber elastomer, 90 parts by weight of a phenolic epoxy resin, 7 parts by weight of a functional resin of formula (I), wherein n is 2, R1 and R2 are both -O-, R3 is an epoxy group with a carbon chain length of 3 and an epoxy equivalent of 271, 15 parts by weight of β-hydroxymethyldiethylenetriamine, 8 parts by weight of p-tert-butylphenyl glycidyl ether, 0.6 parts by weight of a dicyandiamide-urea complex modifier and 0.4 parts by weight of imidazole are added to 30 parts by weight of propylene glycol methyl ether and stirred for 1.8 hours to mix evenly to obtain a resin composition.

[0064] The resin composition was uniformly coated on a glass fiber cloth and baked at 130° C. to obtain a prepreg.

[0065] Four layers of semi-cured sheets are stacked to form a semi-cured layer, and release films are laid on both sides of the semi-cured layer. The semi-cured layer is placed in a mold for curing and molding at a pressure of 1 MPa and a mold temperature of 125°C. After complete curing, the release film is removed to obtain a composite material.

[0066] The test results of the composite material of this embodiment are shown in Table 1.

[0067] Example 3

[0068] 3.5 parts by weight of hydroxy-terminated nitrile rubber were fully stirred and dissolved in propylene glycol methyl ether, and then 78 parts by weight of silicon dioxide were added and stirred at high speed to obtain a filler coated with a rubber elastic body.

[0069] A filler coated with a rubber elastomer, 92 parts by weight of a bisphenol F epoxy resin, 9 parts by weight of a functional resin of formula (I), wherein n is 2, R1 and R2 are both -O-, R3 is an epoxy group with a carbon chain length of 3 and an epoxy equivalent of 271, 30 parts by weight of methyltetrahydrophthalic anhydride, 6 parts by weight of o-cresol glycidyl ether, 1.5 parts by weight of imidazole, and 0.3 parts by weight of KH550 are added to 30 parts by weight of propylene glycol methyl ether and stirred for 2 hours to mix evenly to obtain a resin composition.

[0070] The resin composition was uniformly coated on a glass fiber cloth and baked at 135° C. to obtain a prepreg.

[0071] Four layers of semi-cured sheets are stacked to form a semi-cured layer, and release films are laid on both sides of the semi-cured layer. The semi-cured layer is placed in a mold for curing and molding. The pressure is 0.5 MPa and the mold temperature is 120°C. After complete curing, the release film is removed to obtain a composite material.

[0072] The test results of the composite material of this embodiment are shown in Table 1.

[0073] Example 4

[0074] 4 parts by weight of polysulfide rubber were fully stirred and dissolved in propylene glycol methyl ether, and then 70 parts by weight of phosphazene were added and stirred at high speed to obtain a filler coated with a rubber elastic body.

[0075] A filler coated with a rubber elastomer, 87 parts by weight of a bisphenol F epoxy resin, 11 parts by weight of a functional resin of formula (I), wherein n is 2, R1 and R2 are both -O-, R3 is an epoxy group with a carbon chain length of 3 and an epoxy equivalent of 271, 40 parts by weight of diaminodiphenyl sulfone, 13 parts by weight of phenyl glycidyl ether, 1.7 parts by weight of imidazole and 0.2 parts by weight of KH550 are added to 30 parts by weight of propylene glycol methyl ether and stirred for 2 hours to mix evenly to obtain a resin composition.

[0076] The resin composition was uniformly coated on a glass fiber cloth and baked at 135° C. to obtain a prepreg.

[0077] Four layers of semi-cured sheets are stacked to form a semi-cured layer, and release films are laid on both sides of the semi-cured layer. The semi-cured layer is placed in a mold for curing and molding at a pressure of 1 MPa and a mold temperature of 120°C. After complete curing, the release film is removed to obtain a composite material.

[0078] The test results of the composite material of this embodiment are shown in Table 1.

[0079] Example 5

[0080] 4 parts by weight of polysulfide rubber were fully stirred and dissolved in propylene glycol methyl ether, and then 75 parts by weight of phosphazene were added and stirred at high speed to obtain a flame retardant filler coated with a rubber elastic body.

[0081] A filler coated with a rubber elastomer, 95 parts by weight of a bisphenol A epoxy resin, 15 parts by weight of a functional resin of formula (I), wherein n is 2, R1 and R2 are both -O-, R3 is an epoxy group with a carbon chain length of 3 and an epoxy equivalent of 271, 8 parts by weight of diaminodiphenylmethane, 5 parts by weight of benzyl glycidyl ether, 0.64 parts by weight of a Lewis acid-amine complex, and 0.16 parts by weight of KH550 are added to 30 parts by weight of propylene glycol methyl ether and stirred for 2 hours to mix evenly to obtain a resin composition.

[0082] The resin composition was uniformly coated on a glass fiber cloth and baked at 133° C. to obtain a prepreg.

[0083] Four layers of semi-cured sheets are stacked to form a semi-cured layer, and release films are laid on both sides of the semi-cured layer. The semi-cured layer is placed in a mold for curing and molding at a pressure of 0.8 MPa and a mold temperature of 120°C. After complete curing, the release film is removed to obtain a composite material.

[0084] Example 6

[0085] 2.5 parts by weight of terminal hydroxyl nitrile rubber were fully stirred and dissolved in propylene glycol methyl ether, and then 40 parts by weight of aluminum hydroxide and 20 parts by weight of triester phosphate were added and stirred at high speed to obtain a filler coated with a rubber elastomer.

[0086] A filler coated with a rubber elastomer, 100 parts by weight of PES-901 epoxy resin, 5 parts by weight of a functional resin of formula (II), wherein n is 2, R1 and R2 are both -O-, R3 is an epoxy group with a carbon chain length of 3 and an epoxy equivalent of 221, 2.6 parts by weight of modified dicyandiamide, 5 parts by weight of benzyl glycidyl ether, 1 part by weight of boron trifluoride-amine complex, 0.5 parts by weight of isocyanate-modified imidazole, 0.5 parts by weight of KH560 and 0.05 parts by weight of BYK-W-90 are added to 60 parts by weight of propylene glycol methyl ether, stirred for 2 hours and mixed evenly to obtain a resin composition.

[0087] The resin composition was uniformly coated on a glass fiber cloth and baked at 125° C. to obtain a prepreg.

[0088] Four layers of semi-cured sheets are stacked to form a semi-cured layer, and release films are laid on both sides of the semi-cured layer. The semi-cured layer is placed in a mold for curing and molding at a pressure of 0.5 MPa and a mold temperature of 130°C. After complete curing, the release film is removed to obtain a composite material.

[0089] The test results of the composite material of this embodiment are shown in Table 1.

[0090] Table 1

[0091]

[0092] Example 7

[0093] The difference between Example 7 and Example 1 is that the functional resin is as shown in formula (I), wherein n is 1, R3 is methyl, the epoxy functionality is 1, and the epoxy equivalent is 244.

[0094] The test results of the composite material of this embodiment are shown in Table 2.

[0095] Example 8

[0096] The difference between Example 8 and Example 1 is that the functional resin is as shown in formula (I), wherein R3 is an epoxy group with a carbon chain length of 6 and an epoxy equivalent of 314.

[0097] The test results of the composite material of this embodiment are shown in Table 2.

[0098] Example 9

[0099] The difference between Example 9 and Example 1 is that the functional resin is as shown in formula (Ⅰ), wherein R1 is -O-CH2-CH2-, R3 is pentyl, the epoxy functionality is 1, and the epoxy equivalent is 314.

[0100] The test results of the composite material of this embodiment are shown in Table 2.

[0101] Table 2

[0102]

[0103] Example 10

[0104] The difference between Example 10 and Example 1 is that the epoxy diluent is ethylene glycol diglycidyl ether.

[0105] The test results of the composite material of this embodiment are shown in Table 3.

[0106] Embodiment 11

[0107] The difference between Example 11 and Example 1 is that the epoxy diluent is allyl glycidyl ether.

[0108] The test results of the composite material of this embodiment are shown in Table 3.

[0109] Example 12

[0110] The difference between Example 12 and Example 1 is that the amount of epoxy diluent benzyl glycidyl ether used is 5 parts by weight, and the amount of filler phosphazene used is 40 parts by weight.

[0111] The test results of the composite material of this embodiment are shown in Table 3.

[0112] Embodiment 13

[0113] The difference between Example 13 and Example 1 is that the amount of epoxy diluent benzyl glycidyl ether used is 6 parts by weight, and the amount of filler phosphazene used is 96 parts by weight.

[0114] The test results of the composite material of this embodiment are shown in Table 3.

[0115] Table 3

[0116]

[0117] Embodiment 14

[0118] The difference between Example 14 and Example 1 is that no curing accelerator is added.

[0119] The test results of the composite material of this embodiment are shown in Table 4.

[0120] Embodiment 15

[0121] The difference between Example 15 and Example 1 is that the curing accelerator is selected from 0.06 parts by weight of Lewis acid-amine complex and 0.14 parts by weight of imidazole.

[0122] The test results of the composite material of this embodiment are shown in Table 4.

[0123] Example 16

[0124] The difference between Example 16 and Example 1 is that the curing accelerator is selected from 0.17 parts by weight of Lewis acid-amine complex and 0.03 parts by weight of imidazole.

[0125] The test results of the composite material of this embodiment are shown in Table 4.

[0126] Table 4

[0127]

[0128]

[0129] Embodiment 17

[0130] The difference between Example 17 and Example 1 is that the surface of the filler phosphazene is not coated with the rubber elastomer.

[0131] The test results of the composite material of this embodiment are shown in Table 5.

[0132] Embodiment 18

[0133] The difference between Example 18 and Example 1 is that the amount of rubber elastomer nitrile-isocyanate used is 0.5 parts by weight, and the mass ratio of the coating layer formed therefrom to the filler is 1:188.

[0134] The test results of the composite material of this embodiment are shown in Table 5.

[0135] Embodiment 19

[0136] The difference between Example 19 and Example 1 is that the amount of rubber elastomer nitrile-isocyanate used is 10 parts by weight, and the mass ratio of the coating layer formed thereby to the filler is 1:9.4.

[0137] The test results of the composite material of this embodiment are shown in Table 5.

[0138] Table 5

[0139]

[0140] Embodiment 20

[0141] The difference between Example 20 and Example 1 is that no curing accelerator is added and the surface of the filler is not coated with the rubber elastomer.

[0142] The test results of the composite material of this embodiment are shown in Table 6.

[0143] Table 6

[0144]

[0145] Comparative Example 1

[0146] The difference between Comparative Example 1 and Example 17 is that no functional resin is added.

[0147] The test results of the composite material of this comparative example are shown in Table 7.

[0148] Comparative Example 2

[0149] The difference between Comparative Example 2 and Example 17 is that the functional resin is as shown in formula (I), wherein n is 10 and R3 is an epoxy group with a carbon chain length of 6.

[0150] The test results of the composite material of this comparative example are shown in Table 7.

[0151] Comparative Example 3

[0152] The difference between Comparative Example 3 and Example 17 is that the functional resin is as shown in formula (I), wherein R1 is a non-electron donating group carbonyl.

[0153] The test results of the composite material of this comparative example are shown in Table 7.

[0154] Comparative Example 4

[0155] The difference between Comparative Example 4 and Example 17 is that the functional resin is represented by formula (III):

[0156]

[0157] Where n is 2.

[0158] The test results of the composite material of this comparative example are shown in Table 7.

[0159] Table 7

[0160]

[0161]

[0162] Comparative Example 5

[0163] The difference between Comparative Example 5 and Example 17 is that no epoxy diluent is added.

[0164] The test results of the composite material of this comparative example are shown in Table 8.

[0165] Comparative Example 6

[0166] The difference between Comparative Example 6 and Example 17 is that the epoxy diluent is glycidyl 12-14 alkyl ether with a molecular weight of 770.

[0167] The test results of the composite material of this comparative example are shown in Table 8.

[0168] Comparative Example 7

[0169] The difference between Comparative Example 7 and Example 17 is that the epoxy diluent is cardanol glycidyl ether with a molecular weight of 480.

[0170] The test results of the composite material of this comparative example are shown in Table 8.

[0171] Table 8

[0172]

[0173] The tests of the composite materials in the above embodiments and comparative examples are as follows:

[0174] The test method for bonding is as follows: the fully cured composite material is cut into 2mm wide strips, and the upper and lower sides of the strips are clamped by a universal tensile testing machine. The average stress of peeling 5cm from the upper and lower sides is tested at a speed of 50mm / min, which is the interlayer bonding.

[0175] Curing rate characterization method: at the same curing temperature of 130℃, control different curing times to ensure ΔT g ≤3℃, record the curing time required for △tg≤3℃, the shorter the curing time, the faster the curing rate; Among them, the glass transition temperature T1 and glass transition temperature T2 of the composite material are tested by differential scanning calorimeter, and ΔT g =T2-T1.

[0176] Dispersion: A sample was obtained by pressing and curing a 10cm*10cm prepreg sheet, and the sample was evenly cut into 10 small pieces. The density of each small piece was accurately weighed using a density balance, and the data was recorded. The density variance of the sample was calculated using the variance calculation formula and recorded as D(ρ). The smaller the D(ρ) value, the more uniform the density of the prepreg and the better the dispersion of the filler.

[0177] The composite material prepared by the resin composition of the present application has a bonding performance of ≥15N and a dispersion of ≤10*10 -4 , indicating that the filler in the resin composition has good dispersibility, and the composite material prepared by using the resin composition has a high degree of curing and excellent bonding.

[0178] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0179] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A resin composition, characterized in that It comprises epoxy resin, functional resin, epoxy diluent, filler and curing agent; wherein the molecular weight of the epoxy diluent is ≤270, and the structural formula of the functional resin is as shown in formula (I) or formula (II): In formula (I) and formula (II), n is an integer of 1 to 3, R1 and R2 are electron-donating groups, and R3 is an alkyl group, epoxy group or carboxyl group with a carbon chain length of ≤4.

2. The resin composition according to claim 1, characterized in that The epoxy functionality of the functional resin is ≥2 and / or the epoxy equivalent is ≤300; And / or, R1 and R2 are independently selected from -O-, acyloxy or alkoxy.

3. The resin composition according to claim 1, characterized in that The epoxy diluent has a benzene ring structure in its molecular chain and contains only one terminal epoxy group.

4. The resin composition according to claim 3, characterized in that The epoxy diluent is selected from at least one of benzyl glycidyl ether, phenyl glycidyl ether, o-cresol glycidyl ether or p-tert-butylphenyl glycidyl ether.

5. The resin composition according to claim 1, characterized in that Based on 85 to 95 parts by weight of the epoxy resin, the amount of the functional resin is 5 to 15 parts by weight, the amount of the filler is 40 to 100 parts by weight, the amount of the curing agent is 2 to 40 parts by weight, and the amount of the epoxy diluent is 5 to 15 parts by weight.

6. The resin composition according to claim 5, characterized in that The mass ratio of the epoxy diluent to the filler is 1:10 to 1:

15.

7. The resin composition according to any one of claims 1 to 6, characterized in that The surface of the filler also has a coating layer composed of a rubber elastic body; And / or, the resin composition further comprises a curing accelerator.

8. The resin composition according to claim 7, characterized in that The rubber elastomer is selected from at least one of hydroxy-terminated nitrile rubber, carboxyl-terminated nitrile rubber, polysulfide rubber, polyurethane rubber, polybutadiene core-shell rubber, nitrile-isocyanate or amino polyamide.

9. The resin composition according to claim 7, characterized in that The mass ratio of the coating layer to the filler is 1:10 to 1:

100.

10. The resin composition according to claim 7, characterized in that The curing accelerator is selected from at least one of tertiary amines, Lewis acid-amine complexes, dicyandiamide-urea complex modifiers, phenol, imidazole, imidazole derivatives, and acetylacetone metal complexes.

11. The resin composition according to claim 10, characterized in that The curing accelerator is selected from imidazole derivatives; or, in terms of mass fraction, the curing accelerator contains 50% to 80% of at least one of Lewis acid-amine complex, dicyandiamide-urea complex modification or acetylacetone metal complex.

12. A prepreg made from the resin composition according to any one of claims 1 to 11.

13. A composite material made of the prepreg as claimed in claim 12.